KAJIAN EKONOMI MENGGUNAKAN METODE DISCOUNTED CASH FLOW PADA PENAMBANGAN BATUBARA DI PIT A PT XYZ - Sri Hartati; Kemas Moh Ade Isnaeni (Bajang Institute, 2023)
Companies engaged in the coal mining industry are one of the capital-intensive and high-risk industries. Pit A of PT XYZ which is located in the Mekar Jadi Village area, Kec. Sungai Lilin, Kab. Musi Banyuasin, South Sumatra is one of the actors from the coal mining industry that will conduct a feasibility study. The company will reopen mining in Pit A with the current condition of increasing coal prices, because the Pit is still considered economical in accordance with current coal prices. Discounted Cash Flow (DCF) is a cash flow calculation method that takes into account the time value of money where the money invested at this time will be different in value in the future. With the current selling price of coal, the revenue is 999,847,284 USD/ton with total reserves of 43,436,214 tons. The costs incurred consisted of operating costs of 974,706,736 USD and depreciation of 1,114,983 USD, so the total costs incurred were 480,081,316 USD. The initial investment cost is 1,114,983 USD which depreciates annually. Depreciation in 2023 worth USD 124,436 per year which is valid for 5 years with a total of USD 627,178 and in 2024 doing jetty construction with a value of USD 97,561 per year which is valid for 5 years with a total of USD 487,805 subject to 25% tax. Based on the calculation of the Discounted Cash Flow (DCF) obtained for 3,933,706 USD with a WACC value of 10% and a Net Present Value (NPV) of 2,818,723 USD. An NPV value greater than 0 means that the project will benefit (profit) if it is executed. Based on the calculations in this study that in Pit A PT located in Mekar Jadi Village, Kec. Sungai Lilin, Kab. Musi Banyuasin, South Sumatra deserves to be re-mined because the NPV obtained is greater than 0 which is 2,818,723 USD